2012
DOI: 10.1007/s13758-011-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Cellular Uptake of Mixed-Monolayer Protected Nanoparticles

Abstract: Nanoparticles (NPs) are gaining increasing attention for potential application in medicine; consequently, studying their interaction with cells is of central importance. We found that both ligand arrangement and composition on gold nanoparticles play a crucial role in their cellular internalization. In our previous investigation, we showed that 66-34OT nanoparticles coated with stripe-like domains of hydrophobic (octanethiol, OT, 34%) and hydrophilic (11-mercaptoundecane sulfonate, MUS, 66%) ligands permeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(95 citation statements)
references
References 37 publications
6
89
0
Order By: Relevance
“…It is noteworthy that these NPs do not affect cell division or metabolism, while the growth rate is reportedly reduced by other magnetic nanoparticles agents. 5,18,19,54 More importantly, these results are confirmed by MRI. Indeed we were able to detect the NPs in daughter cells, in similarly prepared samples (Figure 5c).…”
Section: Bioconjugate Chemistrysupporting
confidence: 56%
See 2 more Smart Citations
“…It is noteworthy that these NPs do not affect cell division or metabolism, while the growth rate is reportedly reduced by other magnetic nanoparticles agents. 5,18,19,54 More importantly, these results are confirmed by MRI. Indeed we were able to detect the NPs in daughter cells, in similarly prepared samples (Figure 5c).…”
Section: Bioconjugate Chemistrysupporting
confidence: 56%
“…The quantitative analysis of fluorescent nanoparticle uptake is performed with MetaMorph 7.7 (2011 Molecular Devices) as reported. 19 ■ ASSOCIATED CONTENT …”
Section: Bioconjugate Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…[38][39][40][41] We have also shown that they can carry oligonucleotide cargos into tumor cells under these conditions. 42 Notably, particle entry into cells was observed without any experimental evidence of membrane poration or disruption.…”
Section: Introductionmentioning
confidence: 85%
“…When the ligands were arranged as stripes, the particles were able to translocate easily across the membrane, while in the random arrangement endocytosis occurred. [147][148][149] Endocytosis serves to absorb molecules from the extracellular space by invagination of the plasma membrane and formation of intracellular vesicles. The first type of endocytosis discovered was clathrin-mediated endocytosis, but in the meantime several additional types of endocytosis have been identified.…”
Section: Mechanisms Of Cellular Entrymentioning
confidence: 99%